Psychological health as a mediator in the association between diet and upper gastrointestinal cancer: insights from a large-scale population-based screening project - Yueying Zhang; Shanrui Ma; Xinqing Li; Shaoming Wang; Wenqiang Wei (The Lancet Regional Health. Western Pacific, 2025)
Background: Upper gastrointestinal (UGI) cancer, including esophageal cancer and gastric cancer, poses a significant global health burden. While unhealthy dietary patterns are recognized risk factors, increasing attention is being paid to the role of psychological disorders, such as anxiety and depression, due to their growing prevalence and links to cancer. However, the interplay between diet and psychological health in contributing to UGI cancer and the complex pathways remain underexplored. Our study aims to investigate the association between dietary quality and UGI cancer, with a test of the linking role of depression and anxiety symptoms. Methods: Data were drawn from the baseline survey of the National Cohort of Esophageal Cancer study, conducted between 2017 and 2019 in five high-risk regions of China (Linzhou, Cixian, Feicheng, Yangzhong, Yanting) among residents aged 40–69. Demographic characteristics, dietary information, and psychological conditions were collected using standardized questionnaires by trained staff. Dietary quality was assessed using the Diet Balance Index-16 (DBI-16), which measures inadequate intake (Low Bound Score, LBS), excessive intake (High Bound Score, HBS), and overall diet quality (Dietary Quality Distance, DQD). Psychological symptoms, including anxiety and depression symptoms, were evaluated using the Generalized Anxiety Disorder 7-item Scale (GAD-7) and the Patient Health Questionnaire (PHQ-9). Eligible participants underwent endoscopy screenings, and suspicious cases were confirmed via pathological biopsies. Findings: Among 29,069 participants, 434 UGI cancer cases were confirmed. Logistic regression models indicated that poor diet quality, reflected by inadequate intake (LBS) and unbalanced diet (DQD), was significantly associated with psychological symptoms (e.g., LBS and anxiety: OR=1.36, 95% CI: 1.19-1.56). Meanwhile, compared to the healthy group, UGI cancer participants had more severe psychological distress (e.g., Anxiety and UGI cancer: OR=1.20, 95% CI: 1.14-1.26). Path analysis further revealed that psychological symptoms significantly mediate the relationship between poor dietary quality and UGI cancer risk (e.g., LBS to anxiety: b=0.28, 95% CI: 0.20-0.36; anxiety to UGI lesions: b=0.18, 95% CI: 0.16-0.20). Conversely, excessive intake (HBS), was inversely associated with psychological symptoms and UGI cancer. Interpretation: Our study provides novel insights into the potential mediating role of psychological health, including anxiety and depression symptoms, on the association between dietary quality and UGI cancer. A new comprehensive prevention and control strategy that integrates biopsychosocial healthcare is needed in public education, tertiary prevention, primary healthcare, and clinical practice to reduce the burden of UGI cancer.